2016
DOI: 10.1097/igc.0000000000000620
|View full text |Cite
|
Sign up to set email alerts
|

Functional Impairment and Physical Activity Adherence Among Gynecologic Cancer Survivors

Abstract: Gynecologic cancer survivors do not meet physical activity guidelines and experience functional impairment, which is associated with lower adherence to physical activity recommendations. Prospective studies are needed to better elucidate the relation between functional impairment and physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…3 Beyond the burden of OC, most OC survivors have comorbidities 4,5 and are overweight or obese. 5Y7 Between 50% and 80% report insufficient participation in physical activity (PA), 4,5,7,8 with initial reports suggesting impaired physical function in this population. 8,9 However, most studies to date have assessed PA and physiological characteristics with self-report measures in heterogeneous groups of OC survivors involving women with diverse stages of disease and treatment regimens across varied time points in the disease trajectory.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Beyond the burden of OC, most OC survivors have comorbidities 4,5 and are overweight or obese. 5Y7 Between 50% and 80% report insufficient participation in physical activity (PA), 4,5,7,8 with initial reports suggesting impaired physical function in this population. 8,9 However, most studies to date have assessed PA and physiological characteristics with self-report measures in heterogeneous groups of OC survivors involving women with diverse stages of disease and treatment regimens across varied time points in the disease trajectory.…”
mentioning
confidence: 99%
“…5Y7 Between 50% and 80% report insufficient participation in physical activity (PA), 4,5,7,8 with initial reports suggesting impaired physical function in this population. 8,9 However, most studies to date have assessed PA and physiological characteristics with self-report measures in heterogeneous groups of OC survivors involving women with diverse stages of disease and treatment regimens across varied time points in the disease trajectory. 10 As a result, consequences of OC and its treatment on objectively measured activity behaviors (PA and sedentary behavior), physical function, body composition, and muscle morphology (cross-sectional area and density) remain largely undefined.…”
mentioning
confidence: 99%
“…Another study found that gynecologic cancer survivors with functional impairment were less likely to meet physical activity guidelines. 29 These findings emphasize the importance of women's physical health at the early phases of the cancer trajectory. Nevertheless, 23% of participants indicated during treatment as their preferred time to start a physical activity program, suggesting that this is an acceptable time to offer such programs.…”
Section: Discussionmentioning
confidence: 92%
“…Participants were considered functionally impaired if they responded yes to 1 or both questions regarding limitations in activities and use of special equipment due to health problems. 73 Self-rated functional impairment in OC survivors is associated with lower physical activity levels, 36,73 older age, 15 obesity, 36 comorbidities, fatigue, 74 peripheral neuropathy, 35 and increased psychological distress. 75 Physical function has seldom been objectively measured in OC research.…”
Section: Physical Fitness and Functionmentioning
confidence: 99%
“…In comparison to 27% of women and 35% of women in high-income countries, worldwide, 77 50% to 80% of OC survivors reported insufficient physical activity levels (ie, G150 minutes of moderate and vigorous physical activity per week) or a sedentary lifestyle (ie, no moderate and vigorous physical activity per week) after treatment completion. 34,36,43,73 Research suggests that most women decrease physical activity levels after diagnosis, 78 and many do not return to prediagnosis levels. 79 Interestingly, OC survivors' participation rates in RE (ie, exercise that involves performing sets of repeated movements against a resistance, such as lifting weights) 80 have not been previously reported.…”
Section: Physical Activity Participationmentioning
confidence: 99%